An adsorptive study of Pb(II), Cr(VI) ions and methylene blue dye by treated and untreated coral limestones in aqueous solution - Nkutha, Cynthia Sibongile (Vaal University of Technology, 2021)
For centuries the contamination of surface water has been problematic, especially in third world countries whereby socio-economic issues are prevalent. With the development of various technologies for surface water rehabilitation, adsorption has been found to be the most viable due to its lower cost implications. As such the development of innovative adsorbents which are synergistic to the low cost method have been sought. Herein, the use of fossil coral limestone from Mauritius as adsorbents for the removal of Pb(II), Cr(VI) and methylene blue is presented. The pristine material (PCLS) was thermally treated by calcination to temperatures 800°C (CLS-800) and 900°C (CLS-900) and chemically treated by using an acid HCl (ACL) and base NaOH (BCL). The optimum conditions found for chemical and thermal treatment of the pristine material were used for the one pot synthesis of magnetite and maghemite calcium carbonate based nanocomposites. The pristine fossil coral limestones were characterized by scanning electron microscopy (SEM), energy dispersive X-ray (EDS), X-ray fluorescence XRF), X-ray diffractometer (XRD), Brunauer, Emmett and Teller (BET) and Fourier transformed infrared (FTIR) spectroscopy, UV visible spectrophotometer (UV/vis) and Photolumiscent spectroscopy (PL). Surface morphology of the material was found to contain an interconnected framework of pores, with a surface area of 20.45 m2/g and pore with of 4.04 nm. Thermal treatment of the material was found to increase the surface area of the materials to 64.10 and 63.28 m2/g for CLS-800 and CLS-900. The surface morphology of the calcined materials compared to the pristine were fibrous like and irregularly shaped for CLS-800 and CLS-900 respectively. The FTIR revealed the dominant surface groups to be (-C-O) and (-C=O) asymmetric stretch of the in and out of plane bend of carbonate (-CO32-), with the composition of the material being 91.76 % (-CaO) and 3.32% SrO. The thermally treated materials also exhibited vibrations of asymmetric stretch, which are characteristics of the carbonates as with the pristine material. However, EDS of the pristine compared to that of the calcined materials show a decline in the carbon and oxygen content, due to calcination. The XRD analysis confirmed the orthorhombic structure of aragonite, while CLS-800 was rhombohedral calcite with newly developed (-CaO) peaks. CLS-900 showed complete removal of CaCO3 polymorphs with more (-CaO) peaks. The surface morphology of the chemically modified samples show irregularly shaped surface. The XRD analysis confirmed that chemical treatment did convert the materials to a different polymorph. The FTIR of the chemically modified materials compared to the pristine, were found to reveal a removal of the vibrations of the asymmetric stretch associated with carbonates. However, vibrations associated with (-CaO) were observed. The SEM of the nanocomposites was observed to deviate from sphericity with variable size distribution. The materials were both red and blue shifted due to their variable sizes. Their UV/vis revealed absorption bands in the visible region. The adsorption analysis was done by varying parameters such as time, pH, concentration and temperature. The data was such that the highest capacity for the pristine material was found to be 37.24, 39.26 and 69.42 mg/g for MB, Pb(II) and Cr(VI) respectively. The removal of MB and Pb(II) pollutants were due to physical adsorption, as observed from the good fitting to pseudo first order model (PFOM). The removal of Cr(VI) was due chemisorption and the good fit on pseudo second order model (PSOM). The adsorption process was supported on a heterogeneous surface whereby multilayer adsorption could occur. Adsorption was spontaneous and feasible, exothermic for MB and Pb(II) and endothermic for Cr(VI) at all the studied temperatures as observed from thermodynamics. The adsorption of methylene blue was found to be more favourable on adsorption compared to photo-degradation Chemical modification was observed to increase adsorption and the maximum removal capacities for PCLS, ACL and BCL for Cr(VI) ions were 69.42, 65.04, 64.88 mg/g, Pb(II) ions 39.36, 74.11, 78.34 mg/g and methylene blue 37.24, 46.28, 46.39 mg/g, respectively. Uptake of Cr(VI) and methylene blue on ACL and BCL was feasible on a heterogeneous surface whereby multilayer adsorption took place. Monolayer adsorption on a homogenous surface of ACL and BCL was observed for Pb(II) uptake. The uptake of Pb(II) was exothermic on PCLS and ACL while methylene blue only on PCLS. The adsorption of Cr(VI) ions onto PCLS, ACL and BCL and methylene blue dye onto ACL and BCL were endothermic in nature. The adsorption process was spontaneous and feasible at all the studied temperatures. Thermal modification further increased the adsorption uptake of the pollutants. The recorded uptake for Cr(VI) and Pb(II) were 99.12 and 98.42 mg/g onto CLS-800 and CLS-900, respectively. The adsorption process was found to be physisorption, due to the good fit on PFOM. In addition, the adsorption occurred on a heterogeneous surface whereby multilayer adsorption was possible. The removal of Cr(VI) was found to be exothermic for both the materials and Pb(II) was found to be endothermic. The materials were tested for their reusability to up to four cycles, whereby the removal on the fourth cycle were 16.87, 63.60, 73.13 mg/g for Cr(VI), 9.87, 64.19 and 70.95 mg/g for Pb(II) on PCLS, CLS-800 and CLS-900. While the leaching test for PCLS, CLS-800 and CLS-900 for the release of Ca2+ into solution was found to be within the permissible limits of world health organisation (WHO). The as synthesized nanocomposites increase adsorption of the pollutants. Maximum capacities were found to be 345.34, 388.31, 377.92 and 375.35 mg/g for Pb(II) onto magnetite-PCLS, magnetite-CLS, maghemite-PCLS and maghemite-CLS, respectively and 308.01, 335.3, 335.29 and 335.27 mg/g for Cr(VI) onto magnetite-PCLS, magnetite-CLS, maghemite-PCLS and maghemite-CLS, respectively. From the data it was observed that the maghemite samples were much more favourable for the removal of the pollutants. The removal was due to chemical adsorption, as observed from the good fit onto PSOM and intraparticle diffusion (IPD), whereby surface adsorption was the rate limiting step. The adsorption process was heterogeneous and multilayer, while thermodynamic data reveal that adsorption was spontaneous and favourable at the studied temperature.
M. Tech. (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Coral limestones; Adsorption; Lead ions; Methylene blue dye; Chromium; Acid treatment; Base treatment; Calcined coral limestones; Magnetic nanocomposites; Dissertations, Academic -- South Africa.; Water -- Pollution.; Nanocomposites (Materials).; Adsorption.; Water -- Purification -- Adsorption.